A Translation Analysis Of Independent Clause In Harry Potter And The Sorcerer's Stone And Its Translation - Yafi, Mohammad Ali; , Dr. Dwi Haryanti, M.Hum; , Aryati Prasetyarini, S. Pd., M. Pd (2015)
The research paper studies about the translation analysis of independent clause in compound sentence in novel Harry Potter and the Sorcerer's Stone. The study aims at classifying the type of independent clause in compound sentence, classifying the strategy used by the translator in transfering the independent clause and describing the equivalence of independent clause in compound sentence in novel Harry Potter and the Sorcerer's Stone. The research paper is a descriptive qualitative research. The object of the study is independent clause found in novel Harry Potter and the Sorcerer's Stone and its translation Harry Potter dan Batu Bertuah. The data are types of independent clauses and the strategies used by the translator in transfering the source language. The data are collected from both books by using documentation method. The researcher applies comparison in analyzing the data of the study. The result of the research shows that there are 4 types of independent clause. From 163 data, there are 160 data or 98,15% data of affirmative translated into affirmative, 1 datum or 0,61% datum of imperative translated into interogative, 2 data or 1,22% data of affirmative not to translated, and 1 datum or 0,61% datum of interogative translated into interogative. Then, the researcher found 7 strategies used by the translator in transfering the source language. From 163 data, there are 87 data or 53,37% data of adoption, 30 data or 18,40% data of deletion, 24 data or 14,72% data of addition, 51 data or 31, 28% data of structural shift, 17 data or 10,42% data of level shift, 2 data or 1,22% data of adaptation and 6 data or 3,68% data of intra-system shift. Besides, the equivalence of translation is divided into equivalent translation and non equivalent translation. In the research paper, all data or 163 data or 100% data belong to equivalent translation. Keywords: translation, independent clause, Harry Potter and the Sorcerer's Stone.